2013
DOI: 10.1016/j.neuroscience.2013.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Proconvulsant actions of intrahippocampal botulinum neurotoxin B in the rat

Abstract: Botulinum neurotoxins (BoNTs) may affect the excitability of brain circuits by inhibiting neurotransmitter release at central synapses. There is evidence that local delivery of BoNT serotypes A and E, which target SNAP-25, a component of the release machinery specific to excitatory synapses, can inhibit seizure generation. BoNT serotype B (BoNT/B) targets VAMP2, which is expressed in both excitatory and inhibitory terminals. Here we assessed the effects of unilateral intrahippocampal infusion of BoNT/B in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…In ESNs, the accelerated intoxication of GABAergic synapses acutely disinhibits network behavior, driving a transition from stochastic firing to prolonged bursts, followed ultimately by network silencing as glutamatergic synapses are intoxicated. Observations of synapse subtype-specific latencies are consistent with in vitro observations of disinhibited network responses following addition of BoNT/A to primary cortical or spinal cord neurons on planar microelectrode arrays (Scarlatos et al, 2008 ; Pancrazio et al, 2014 ) as well as in vivo reports of seizures following the intrahippocampal administration of BoNT/B (Broer et al, 2013 ). The rapid elimination of GABAergic signaling by BoNT/A treatment also suggests that functional assays directly (MIST) or indirectly (network responses) measuring the integrity of inhibitory neurotransmission could be leveraged as highly sensitive, specific and rapid methods to detect the presence of active BoNT.…”
Section: Discussionsupporting
confidence: 78%
“…In ESNs, the accelerated intoxication of GABAergic synapses acutely disinhibits network behavior, driving a transition from stochastic firing to prolonged bursts, followed ultimately by network silencing as glutamatergic synapses are intoxicated. Observations of synapse subtype-specific latencies are consistent with in vitro observations of disinhibited network responses following addition of BoNT/A to primary cortical or spinal cord neurons on planar microelectrode arrays (Scarlatos et al, 2008 ; Pancrazio et al, 2014 ) as well as in vivo reports of seizures following the intrahippocampal administration of BoNT/B (Broer et al, 2013 ). The rapid elimination of GABAergic signaling by BoNT/A treatment also suggests that functional assays directly (MIST) or indirectly (network responses) measuring the integrity of inhibitory neurotransmission could be leveraged as highly sensitive, specific and rapid methods to detect the presence of active BoNT.…”
Section: Discussionsupporting
confidence: 78%
“…This, in turn, renders the hippocampus more vulnerable to epileptiform discharges and their propagation into all-or-none pattern of seizure activity recruiting the whole network. Importantly, analogous reductions of PTZ seizure threshold have previously been documented after decreasing intrinsic or synaptic excitability of hippocampal neurons by elevating NaK-ATPase activity (Funck et al, 2015) or lowering transmitter release (Bröer et al, 2013). Furthermore, we previously observed that mice devoid of the presynaptic active zone protein RIM1␣, which exhibit a decrease in neurotransmitter release in the hippocampal CA1 region, also experience an increased seizure frequency in the chronic phase after pilocarpine-induced SE (Pitsch et al, 2012).…”
Section: Discussionsupporting
confidence: 70%
“…Responses were recorded as 1, the rat has no reaction; 2, the rat turned toward the object; 3, the rat moved away from the object; 4, the rat frozen; 5, the rat turned toward the touch; 6, the rat turned away from the touch; 7, the rat jumped with or without vocalizations [35,37] .…”
Section: Touch-response Testmentioning
confidence: 99%
“…Responses were scored as 1, very easy; 2, easy with vocalizations; 3, some difficulties, the rat reared and faced the hand; 4, frozen (the rat); 5, difficult, the rat avoided the hand by moving away; 6, very difficult, the rat behaved defensively and may attacked the hand [35,37] . The behavioral tests were done by three independent observers, and the means of their scores were calculated for each animal for each test.…”
Section: Pick-up Testmentioning
confidence: 99%